2020
DOI: 10.1186/s12939-020-01195-3
|View full text |Cite
|
Sign up to set email alerts
|

Two-eyed seeing of the integration of oral health in primary health care in Indigenous populations: a scoping review

Abstract: Background: Indigenous people experience significant poor oral health outcomes and poorer access to oral health care in comparison to the general population. The integration of oral health care with primary health care has been highlighted to be effective in addressing these oral health disparities. Scoping studies are an increasingly popular approach to reviewing health research evidence. Two-eyed seeing is an approach for both Western and Indigenous knowledge to come together to aid understanding and solve p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
1
26
0
2
Order By: Relevance
“…(Cape Breton University 2020a) This Mi'kmaw worldview, coined as 'Two-Eyed Seeing' by Elder Marshall (Bartlett, Marshall, and Marshall 2012), was first introduced to us by Leah Fontaine, an Anishinaabe-Métis-Dakota Indigenous Initiatives Educator (Fontaine and Chen 2018). It has been applied to medical research (McKivett et al 2020), care of the aged (Sivertsen, Harrington, and Hamiduzzaman 2020), oral healthcare (Shrivastava et al 2020), and science education (Gilbert, Onwu, and Mufundirwa 2020;Michie, Hogue, and Rioux 2018). It is shared here with the permission of Elder Marshall, who explains, 'Two-Eyed Seeing adamantly, respectfully, and passionately asks that we bring together our different ways of knowing to motivate people, Aboriginal and non-Aboriginal alike, to use all our understandings so we can leave the world a better place' (336).…”
Section: Participatory Action and The Positionality Of Authorsmentioning
confidence: 99%
“…(Cape Breton University 2020a) This Mi'kmaw worldview, coined as 'Two-Eyed Seeing' by Elder Marshall (Bartlett, Marshall, and Marshall 2012), was first introduced to us by Leah Fontaine, an Anishinaabe-Métis-Dakota Indigenous Initiatives Educator (Fontaine and Chen 2018). It has been applied to medical research (McKivett et al 2020), care of the aged (Sivertsen, Harrington, and Hamiduzzaman 2020), oral healthcare (Shrivastava et al 2020), and science education (Gilbert, Onwu, and Mufundirwa 2020;Michie, Hogue, and Rioux 2018). It is shared here with the permission of Elder Marshall, who explains, 'Two-Eyed Seeing adamantly, respectfully, and passionately asks that we bring together our different ways of knowing to motivate people, Aboriginal and non-Aboriginal alike, to use all our understandings so we can leave the world a better place' (336).…”
Section: Participatory Action and The Positionality Of Authorsmentioning
confidence: 99%
“…Spirituality is strong, and there is a lot of social support, and a strong sense of community mediated oral health behaviour that are beneficial. Individuals' health may be influenced by religious devotion to a social media platform and participant assistance, which could improve health related behaviour through more fast dissemination of health information and higher participation [5]. Individuals' health may be influenced by religious devotion to a social media platform and participant assistance, which could improve health-related behaviour through more fast dissemination of health information and higher participation coping with anxiety [6].…”
Section: Social Support and Health Behaviourmentioning
confidence: 99%
“…Second is Emotional well-being refers to becoming conscious of and tolerant of one's feelings and moods third is Physical Wellness and fourth is Social Wellness It helps people realize their greatest potential, find meaning and purpose in life, and find fulfillment from within. Self-actualization, transcendence, and selfevolution are all ways to achieve this condition of being [2]. The fourth component of health is spiritual well-being.…”
Section: Insight Into Spiritual Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many researchers have attempted to expand basic microbiological models for ECC development, and to include various social, demographic and behavioural factors such as ethnicity, family income, maternal education level, family status, and parental knowledge (2). Children from the minority ethnic groups or immigrant children (3) have been found to be at higher risk of caries, too. Numerous studies suggested that ECC was more commonly found in children who lived in poverty (4), who were of ethnic and racial minorities (3), from single parent family (5), with parents of low educational level, especially those of illiterate mothers (6).…”
Section: Introductionmentioning
confidence: 99%